ION ASSOCIATION OF DILUTE AQUEOUS POTASSIUM CHLORIDE AND POTASSIUM HYDROXIDE SOLUTIONS TO 600°C AND 300 MPA DETERMINED BY ELECTRICAL CONDUCTANCE MEASUREMENTS - Ho P.C.; Palmer D.A. (My University, 1997)
The limiting molar conductances (Λ0) and ion association constants of dilute (<0.01 mol . kg-1) aqueous potassium chloride and hydroxide solutions were determined by electrical conductance measurements from 200 to 600°C and from 100 to 600°C, respectively, and pressures up to 300 MPa. The limiting molar conductances of KOH(aq) increase with increasing temperature up to 300°C and decreasing density. Above 400°C and densities between 0.8 and 0.4 g . cm-3 for KCl(aq) and between 0.8 and 0.6 g . cm-3 for KOH(aq), Λ0 is nearly temperature-independent but increases linearly with decreasing density. The molal ion association constants (KA(m)) for both KCl(aq) and KOH(aq) increase with increasing temperature and decreasing solution density. At corresponding temperatures and densities, ion association of KCl(aq) is similar in extent to NaCl(aq), whereas for KOH(aq) the values are slightly lower than for NaOH(aq). The log KA(m) values for KCl(aq) and KOH(aq) were calculated using the Shedlovsky equation exclusively from data obtained at temperatures =<400°C and can be represented as functions of temperature (T, Kelvin) and the logarithm of water density (ρw, g . cm-3) as follows: log KA(m) (KCl) = 0.753 - 100.21/T - (10.316 - 3598.9/T) log ρw and log KA(m) (KOH) = 1.183 - 132.61/T - (13.002 - 6216.8/T) log ρw These expressions apply strictly at ρw =< 0.4 g . cm-3 where the measurements are most precise.